Kuat Tekan Dan Kuat Tarik Belah Beton OPC Dan OPC POFA Dengan Air Gambut Sebagai Air Pencampur Dan Air Perendaman - Bobby Ansyari; Ismeddiyanto Ismeddiyanto; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research aim to obtain the mechanical properties of OPC and OPC POFA concrete by using peat water as mixing and curing water to simulate peat field condition. The specimens were cured for 28 days directly in peat water canal. Mechanical properties tests such as compressive and tensile strength were tested for 7 and 28 days. Results of this research at 28th days show that peat field condition was increase compressive and tensile strength of OPC concrete compared with OPC normal concrete, and results also show that using POFA as subtitution of 10% cement weight was decrease compressive and tensile strength of OPC POFA concrete compared with OPC POFA concrete in normal condition. However, the compressive and tenslie strength of OPC POFA concrete in peat field and normal condition were higher than OPC normal concrete.Keywords : Mechanical properties, OPC, POFA (palm oil fuel ash), peat water, peat field condition.